RISK MANAGEMENT OF WORLD CLASS OPERATIONS IN AFTERMARKET LOGISTICS AT ROLLS ROYCE - Leung, Lily (2005)
This study focused on the risk management on the risks identified when the business policy options are implemented. It is performed by studying the current business process and benchmarking industry practices of the proposed policies. A risk management framework have been recommended and developed based on analysing existing risk management system in R-R. The risk management framework is used to set up a platform for risk management in implementing the proposed polices and detail risks analysis and risk evaluation. Finally, key risk factors have been identified and analysed for each policy and those in common are addressed and countermeasures for potential risk mitigation.